RP-HPLC Method Development and Validation for Estimation of Acebrophylline - Sharma, Bhavik; Agarwal, Sushil Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Chromatography, a separation technique, is mostly used in chemical analysis in which High-performance liquid chromatography (HPLC) is an extremely versatile technique where analytes are separated by passage through a column packed with micrometer-sized particles. Theses day reversed-phase chromatography is commonly used separation technique in HPLC. The reasons for this include the simplicity, versatility, and scope of the reversed-phase method as it is able to handle compounds of a diverse polarity and molecular mass. Reversed phase chromatography has found both analytical and preparative applications in the area of biochemical separation and purification. Molecules that possess some degree of hydrophobic character, such as proteins, peptides and nucleic acids, can be separated by reversed phase chromatography with excellent recovery and resolution. This review covers the importance of RP-HPLC in analytical method development and their strategies along with brief knowledge of critical chromatographic parameters need to be optimized for an efficient method development. Key Words- HPLC, RP-HPLC